The Effectiveness of Extinction and Negative Punishment to Eliminate the Behavior of Rejecting or Choosing Certain Foods in Picky Eaters - Anastia, Shabrina Poetry (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Picky eater is a behavior of refusing to eat and choosing the type of food to be consumed, usually occurs in children under the age of five, but some are also ongoing. The method that can be done to overcome the problem of picky eaters that is still ongoing is by intervention using the extinction and negative punishment methods which are useful for eliminating the behavior of refusing to eat or choosing certain foods. The purpose of this study was to eliminate picky eater behavior in children who experience picky eating that has continued since childhood and has an effect on development. The place of research was at the subject's home. This study was conducted in three stages, namely intake, baseline and treatment. The results of this study indicate that the behavior of refusing and choosing certain foods owned by the subject decreased after being given intervention with the extinction and negative punishment methods.